Expert consensus recommendations to improve diagnosis of ATTR amyloidosis with polyneuropathy - Adams, David (2022)
Amyloid transthyretin (ATTR) amyloidosis with polyneuropathy (PN) is a progressive, debilitating, systemic disease wherein transthyretin protein misfolds to form amyloid, which is deposited in the endoneurium. ATTR amyloidosis with PN is the most serious hereditary polyneuropathy of adult onset. It arises from a hereditary mutation in the TTR gene and may involve the heart as well as other organs. It is critical to identify and diagnose the disease earlier because treatments are available to help slow the progression of neuropathy. Early diagnosis is complicated, however, because presentation may vary and family history is not always known. Symptoms may be mistakenly attributed to other diseases such as chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), idiopathic axonal polyneuropathy, lumbar spinal stenosis, and, more rarely, diabetic neuropathy and AL amyloidosis. In endemic countries (e.g., Portugal, Japan, Sweden, Brazil), ATTR amyloidosis with PN should be suspected in any patient who has length-dependent small-fiber PN with autonomic dysfunction and a family history of ATTR amyloidosis, unexplained weight loss, heart rhythm disorders, vitreous opacities, or renal abnormalities. In nonendemic countries, the disease may present as idiopathic rapidly progressive sensory motor axonal neuropathy or atypical CIDP with any of the above symptoms or with bilateral carpal tunnel syndrome, gait disorders, or cardiac hypertrophy. Diagnosis should include DNA testing, biopsy, and amyloid typing. Patients should be followed up every 6-12 months, depending on the severity of the disease and response to therapy. This review outlines detailed recommendations to improve the diagnosis of ATTR amyloidosis with PN.